An analysis of the implications of uncertainty and agency problems on the wealth effects to acquirers of private firms - Mantecon, Tomas (Journal of Banking & Finance, 2008)
Extensive empirical work shows that bidders do not gain from the acquisition of publicly traded targets but experience positive excess returns in the acquisition of privately held firms. This study investigates how two important differences between private and public firms, namely, informational uncertainty and ownership characteristics, impact the returns to acquirers. A sample of targets that were acquired shortly after filing for an IPO was collected to circumvent the lack of information on private firms. In spite of the special characteristics of these targets, the listing effect is still prevalent in this sample. The results of the analysis are consistent with the hypothesis that acquirers gain in the acquisition of private firms because these targets have a relatively weaker bargaining position due to informational and agency problems and costly access to external capital markets to finance growth opportunities.